2014
DOI: 10.1097/01.tp.0000438025.96334.eb
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant CD8 T-Cell Response to IE-1 Discriminates Seropositive Kidney Recipients at Risk of Developing CMV Infection Posttransplant

Abstract: Assessment of IE-1-specific CD8 T-cell frequencies pretransplant may be a useful tool for identifying seropositive SOT patients at risk of developing CMV infection posttransplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Could there be a mechanism whereby EBV replication protects healthy adults from BKV replication and vice versa? CMV viremia was associated with a decreased incidence of BKV reactivation in kidney transplant recipients in a recent study and while the authors proposed it could be due to reduction in immunosuppression (22); this could have been due to an ongoing protective CD8+ lymphocyte response activated by the preceding CMV (23). Perhaps a similar mechanism could explain our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Could there be a mechanism whereby EBV replication protects healthy adults from BKV replication and vice versa? CMV viremia was associated with a decreased incidence of BKV reactivation in kidney transplant recipients in a recent study and while the authors proposed it could be due to reduction in immunosuppression (22); this could have been due to an ongoing protective CD8+ lymphocyte response activated by the preceding CMV (23). Perhaps a similar mechanism could explain our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed the latest consensus guidelines on HCMV in SOT recommended these methods as an adjunct tool to predict risk of viremia and disease [21]. The HCMV-specific cellular assays have been evaluated in different clinical scenarios: some studies have focused on the T-cell immunity in the pre-transplantation period to potentially predict subsequent viral infection or disease [82][83][84][85][86] (Table 3), many more studies have assessed HCMV-specific cellular responses after transplantation [76,[87][88][89][90][91][92][93][94][95][96][97][98] (Table 4). Few studies have assessed HCMV-specific cell-mediated immunity in large cohorts of high-risk SOT recipients (i.e., donor HCMV-seropositive/recipient HCMV-seronegative) to predict disease development [90].…”
Section: Hcmvmentioning
confidence: 99%
“…Ritta et al and Bestard et al found that having low pretransplant CMV‐specific T‐cell responses was associated with a higher risk of post‐transplant CMV replication . López‐Oliva et al reported that low pretransplant CMV‐specific CD8 + T‐cell counts predicted the development of CMV infection with 100% specificity and 85.7% sensitivity, while Mena‐Romo et al found that patients were more prone to suffer from CMV disease in the absence of detectable pretransplant CMI . More recently, the quantification of pretransplant CMV‐specific T‐cells directed against immediate early (IE)‐1, and/or pp65 antigens has been proven to be useful for the identification of R + kidney transplant recipients at increased risk for CMV‐disease …”
Section: Introductionmentioning
confidence: 99%
“…López‐Oliva et al reported that low pretransplant CMV‐specific CD8 + T‐cell counts predicted the development of CMV infection with 100% specificity and 85.7% sensitivity, while Mena‐Romo et al found that patients were more prone to suffer from CMV disease in the absence of detectable pretransplant CMI . More recently, the quantification of pretransplant CMV‐specific T‐cells directed against immediate early (IE)‐1, and/or pp65 antigens has been proven to be useful for the identification of R + kidney transplant recipients at increased risk for CMV‐disease Allo‐HSCT setting: To our knowledge, no studies have specifically investigated whether the assessment of CMV‐specific CMI may help to correctly classify allo‐HSCT candidates (and their donors) with respect to CMV infection status.…”
Section: Introductionmentioning
confidence: 99%